Specyfika funkcjonowania schronisk górskich w świetle zmian otoczenia gospodarczego i dynamiki rozwoju sektora turystyki w Polsce - Stosik, Aneta; Zarzycki, Piotr; Grobelny, Jacek (The mountain hostess organization in perspective of environment changes and dynamic tourist sector development, 2006)
The article includes organizational and management specification in chosen polish tourist institutions from the perspective of dynamic changes environment. It's cover also the idea organizational progress walking by in new trend's and standards of market economy. Article shows diagnosis 54 tourist subjects of five well marked polish mountain arias; Sudety, Beskid Śląski, Beskid Żywiecki, Tatry and Bieszczady
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 303-309